Effect of proprioceptive neuromuscular facilitation on patients with chronic ankle instability: A systematic review and meta-analysis - Yikun Yin; Jialin Wang; Qihan Lin; Yinghang Luo; Yongsheng Liu; Junzhi Sun (PLoS ONE, 2025)
Objective This study conducts a rigorous meta-analysis of existing literature to rigorously examine the efficacy of Proprioceptive Neuromuscular Facilitation (PNF) in ameliorating functional deficits associated with Chronic Ankle Instability (CAI). Methods Literature searches were conducted in multiple databases including China National Knowledge Infrastructure (CNKI), VIP, Wanfang, China Biology Medicine disc (CBM), PubMed, EBSCO (Medline, CINAHL, SPORTDiscus, and Rehabilitation & Sports Medicine Source), Embase, ScienceDirect, ProQuest, Cochrane Library, and Web of Science for randomized controlled trials assessing the effects of Proprioceptive Neuromuscular Facilitation interventions on patients with Chronic Ankle Instability. The publication timeframe spanned from the inception of each database until April 10, 2024. Meta-analysis was performed using STATA 12 software on the included studies. Results ① A total of 12 randomized controlled trials were included, encompassing 405 patients with Chronic Ankle Instability, demonstrating a generally high methodological quality of the literature.② Meta-analysis results indicate that compared to the control group, Proprioceptive Neuromuscular Facilitation (PNF) significantly enhanced the balance ability of patients with Chronic Ankle Instability as measured by the Y Balance Test (YBT) (Weighted Mean Difference (WMD) = 3.61, 95% CI [2.65, 4.56], z = 7.42, P<0.001) and the Star Excursion Balance Test (SEBT) (WMD = 5.50, 95% CI [3.80, 7.19], z = 6.36, P<0.001), with improvement in all eight directions of SEBT balance ability surpassing that of the control group (P<0.05); muscle strength around the ankle (SMD) = 0.19, 95% CI [0.03, 0.36], z = 2.26, P = 0.024), with both Plantar flexion and Dorsal flexion muscle strength improvements exceeding those of the control group (P<0.05); Visual Analog Scale (VAS) (WMD = -1.39, 95% CI [-1.72, -1.06], z = 8.23, P<0.001); Ankle instability questionnaire (WMD = 2.91, 95% CI [1.92, 3.89], z = 5.78, P<0.001).③Descriptive analysis results showed that the differences in Inversion Joint Position Sense and Dorsiflexion range of motion between the PNF and control groups were not statistically significant (P>0.05), however, the effects of PNF training persisted for a certain period even after cessation of treatment. Conclusion Proprioceptive Neuromuscular Facilitation (PNF) can significantly improve balance, muscle strength, and pain in patients with Chronic Ankle Instability (CAI). While PNF has shown improvements in joint position sense and dorsiflexion range of motion for CAI patients, with effects that remain for a period thereafter, these improvements were not significantly different when compared to the control group. Further research is required to substantiate these specific effects.